Sex differences in exploratory behaviour of the common toad, Bufo bufo. Issue 6 (2nd November 2018) - Ogurtsov, Sergei V.; Antipov, Vladislav A.; Permyakov, Mikhail G.
Abstract : The origin of sex differences in spatial behaviour is widely discussed in the laboratory studies in higher vertebrates, but almost nobody has investigated the problem in the first tetrapods, in amphibians. We tested exploratory behaviour, the crucial element of spatial behaviour, in 12 males and 7 females of the common toad, Bufo bufo, in a rectangular maze with four rooms and visual objects inside. One of the four rooms contained the useful resources (water, food, shelter). In the first 4 hr-trial toads explored the maze with the resources. In the second 4 hr-trial, 15 min later, the same environment contained no resources, and we evaluated the changes in the extent of movements and spatial preferences as the result of exploratory learning. In the first trial females moved widely among the rooms, while males more often visited the room with the resources. However, both sexes spent most of the time in the room with the resources. When the resources disappeared, males increased locomotory activity and the frequency of visits to the rooms. The activity of females remained almost unchanged. Toads were not motivated to search resources directly, as the latency to enter the resource room remained the same in both trials. Instead of this, toads monitored the potential location of the useful resources during the test, but the exploratory strategies of sexes were different. Males travelled mainly in the resource room. Females spent more time and more often visited two rooms: the resource and the opposite one. Thus, males demonstrated more intensive and more goal-oriented exploratory behaviour than females. It is the first evidence of sex differences in exploratory behaviour of amphibians obtained under controlled laboratory conditions.